Singlet oxygen scavenging activity of tocopherol and plastochromanol in Arabidopsis thaliana: relevance to photooxidative stress - Rastogi, Anshu; Yadav, Deepak Kumar; Szymańska, Renata; Kruk, Jerzy; Sedlářová, Michaela; Pospíšil, Pavel (Plant, cell & environment, 2014)
In the present study, singlet oxygen (¹O₂) scavenging activity of tocopherol and plastochromanol was examined in tocopherol cyclase-deficient mutant (vte1) of Arabidopsis thaliana lacking both tocopherol and plastochromanol. It is demonstrated here that suppression of tocopherol and plastochromanol synthesis in chloroplasts isolated from vte1 Arabidopsis plants enhanced ¹O₂ formation under high light illumination as monitored by electron paramagnetic resonance spin-trapping spectroscopy. The exposure of vte1 Arabidopsis plants to high light resulted in the formation of secondary lipid peroxidation product malondialdehyde as determined by high-pressure liquid chromatography. Furthermore, it is shown here that the imaging of ultra-weak photon emission known to reflect oxidation of lipids was unambiguously higher in vte1 Arabidopsis plants. Our results indicate that tocopherol and plastochromanol act as efficient ¹O₂ scavengers and protect effectively lipids against photooxidative damage in Arabidopsis plants.
Keywords: listy rostlin; vysokoúčinná kapalinová chromatografie; intramolekulární transferasy; Plant Leaves; Chromatography, High Pressure Liquid; Singlet Oxygen; Intramolecular Transferases; Arabidopsis; chloroplast; Chloroplasts; chloroplasty; oxidační stres; tokoferoly; spin trapping; singletový kyslík; scavengery volných radikálů; Oxidative Stress; Tocopherols; Spin Trapping; Free Radical Scavengers; EPR spin-trapping